The Relationship between Self-Efficacy and Self-Management among Teenager with Asthma: A Systematic Review - Eva Supriatin; Agus Hendra; Tintin Supriatin; Linlin Lindayani (Universitas Padjadjaran, 2021)
Asthma is a chronic reactive airway disease caused by a variety of variables, one of which is psychological. Adolescents are prone to psychological issues. Adolescents frequently face difficulties and feel frustrated as a result of the conditions they face, but most adolescents employ a variety of strategies to overcome the problems that arise. Self-efficacy can lead to good self-management. To investigate the relationship between self-efficacy and self-management in asthmatic teenagers. The search strategy is to conduct Pubmed and Google Scholar s for articles that have been published. The term